Raba nedoločnih količinskih zaimkov v dveh francosko- slovenskih korpusih - Struna, Tatjana (Vestnik za tuje jezike, 2018)
The article gives a comprehensive analysis of the quantity of indefinite quantifiers in French and Slovene, in which French provided the basis for finding Slovene equivalents. In the corpus based approach the semantic equivalents of indefinite quantifiers are put forward on the basis of a detailed comparison of two French-Slovene corpuses, which yielded a surprisingly large amount of different translation equivalents, the largest quantity of which are represented by the chosen quantifiers. It has been proven that despite the lexical translation equivalents, they can be translated with numerous other equivalents. However, sometimes there is also the possibility to omit the translation of quantifiers in Slovene without losing the meaning of the original French sentence.
Keywords: Evrokorpus (korpus); francoščina; korpusno jezikoslovje; nedoločni kvantifikatorji; nedoločnost; prevodne ustreznice; Spook (korpus); zaimek